46‐2: Invited Paper: Ultimate Resolution Active Matrix Display with Oxide TFT Backplanes for Electronic Holographic Display. Issue 1 (30th May 2018) - Hwang, Chi-Sun; Kim, Yong-Hae; Yang, Jong-Heon; Choi, Ji Hun; Pi, Jae-Eun; Kim, Gi Heon; Hwang, Chi-Young; Choi, Kyunghee; Kim, Hee-Ok; Lee, Won-Jae; Park, Sang-Hee Ko; Kim, Jinwoong
Abstract : Oxide TFT backplane with 1μm channel length was developed for the application to electronic holographic display. Spatial light modulator (SLM) panel with 3μm pixel pitch was designed and successfully fabricated. The resolution of SLM panel was 16K by 3.2K and the diagonal length of active area was 2 inch. Fabricated SLM panel was ECB mode reflective type LCD panel, which could modulate the phase of incident light more than 2π. 3D image was successfully reconstructed with fabricated SLM panel. Vertical channel oxide TFTs are proposed for the switching device of 1μm pixel pitch. Oxide TFTs with ultra short channel length can be an enabler of the active matrix display with ultimate resolution.